Organic ferroelectric opto-electronic memories - Asadi, Kamal; Li, Mengyuan; Blom, P. W. M.; Kemerink, Martijn; Leeuw, Dago M. de (Materials today, 2011)
Memory is a prerequisite for many electronic devices. Organic non-volatile memory devices based on ferroelectricity are a promising approach towards the development of a low-cost memory technology based on a simple cross-bar array. In this review article we discuss the latest developments in this area with a focus on the most promising opto-electronic device concept, i.e., bistable rectifying diodes. The integration of these diodes into larger memory arrays is discussed. Through a clever design of the electrodes we demonstrate light emitting diodes with integrated built-in switches that can be applied in signage applications.